Paul's new moment : continental philosophy and the future of Christian theology - Milbank, John.; Zizek, Slavoj; Davis, Creston (Grand Rapids, MI : Brazos, 2010)
"Are there moments in Christian history when non-Christians in some ways understand Christianity better than Christians?...Today some leading secular thinkers have turned to a surprising source: the apostle Paul. The rediscovery of Paul by atheistic or agnostic European philosophers is one of the most striking recent developments in philosophy--and certainly one of keen interest to the church"--BACK COVER.
On Paul. Paul against biopolitics / John Milbank -- Paul and the truth event / Slavoj Zizek -- Paul and subtraction / Creston Davis -- On the liturgy. Liturgy and the senses / Catherine Pickstock -- Subtractive liturgy / Creston Davis -- A meditation of Michelangelo's Christ on the Cross / Slavoj Zizek -- On mediation and apocalypse. Thinking backward: predestination and apocalypse / Slavoj Zizek -- The return of mediation / John Milbank.
Includes bibliographical references and indexes.
Keywords: Christianity -- Philosophy; Philosophy and religion; Continental philosophy; Philosophical theology